Height to first pod: A review of genetic and breeding approaches to improve combine harvesting in legume crops - Kuzbakova, Marzhan; Khassanova, Gulmira; Oshergina, Irina; Ten, Evgeniy; Jatayev, Satyvaldy; Yerzhebayeva, Raushan; Bulatova, Kulpash; Khalbayeva, Sholpan; Schramm, Carly; Anderson, Peter; Sweetman, Crystal; Jenkins, Colin L. D.; et al. (Frontiers in Plant Science, 2022)
Height from soil at the base of plant to the first pod (HFP) is an important trait for mechanical harvesting of legume crops. To minimise the loss of pods, the HFP must be higher than that of the blades of most combine harvesters. Here we review the genetic control, morphology and variability of HFP in legumes and attempt to unravel the diverse terminology for this trait in the literature. HFP is directly related to node number and internode length, yet through different mechanisms. The phenotypic diversity and heritability of HFP and their correlations with plant height are very high among studied legumes. Only a few publications describe QTL analysis where candidate genes for HFP with confirmed gene expression have been mapped. They include major QTLs with eight candidate genes for HFP, which are involved in auxin transport and signal transduction in soybean as well as MADS box gene SOC1 in Medicago trancatula, and BEBT or WD40 genes located nearby in the mapped QTL in common bean. There is no information available about simple and efficient markers associated with HFP, which can be used for marker-assisted selection for this trait in practical breeding, which is still required in the nearest future. To our best knowledge, this is the first review to focus on this significant challenge for legume-based cropping systems.